Comparison of Extraction Techniques for Pectin from Kinnow Peel by using Convectional, Sonication, and Thermo-Sonication Techniques: Extraction Techniques for Pectin from Kinnow Peel - Sajid, Talha; Hassan, Farazia; Khalid, Muhammad Umair; Mumtaz, Muhammad Soban; Quddoos, Muhammad Yousaf; Mahmood, Shahid; Firdos, Nida; Raza, Muhammad Siddique; Batool, Rida; Irshad, Iqra; Rafique, Ayesha (Futuristic Biotechnology, 2023)
Kinnow is a species of citrus family. Pectin has been declared as a safe substance. However, conventional methods are practiced in some industries for pectin extraction from citrus peel. Innovative techniques like ultrasound-assisted extraction (UAE), sonication, and thermos-sonication may play a vital role in increasing the yield of pectin from peels of citrus. Objective: To conduct a comparative analysis of Kinnow peel pectin extracted through conventional, Sonication, and Thermosonication techniques. Methods: For this purpose raw materials (Kinnow) purchased from the local market of Faisalabad, Kinnow peels were dried and made into fine powder. This fine powder is used further to extract pectin by conventional, sonication and thermos-sonication extraction methods. Results: Different qualitative analyses of pectin like solubility of dry pectin in cold and hot water, and solubility in cold and hot alkali, pH, pectin color, quantitative analysis of pectins like yield and equivalent weight, and methoxyl content. During pectin testing, thermos-sonication techniques proved their excellence. Among all treatments during analysis, Moreover, thermos-sonication was found to be the best extraction technique among all treatments. The yield is maximum (15.55%) through thermo-sonicated extracted samples. The highest value of equivalent weight (345±13.08) was seen in the thermos-sonication-treated sample. The upper limit (5.33±0.12) of methoxyl content was held by thermos-sonication-treated samples. Pectin’s capacity to bind sugar and spreading quality increases with increasing methoxyl content. Conclusions: It was concluded that the best extraction method of pectin is the thermos-sonication method for better qualitative and quantitative output.